Screening of the arrestin gene in dogs afflicted with generalized progressive retinal atrophy - Gabriele Dekomien; Jörg Thomas Epplen (BMC Genetics)
Abstract Background Intronic DNA sequences of the canine arrestin (SAG ) gene was screened to identify potential disease causing mutations in dogs with generalized progressive retinal atrophy (gPRA). The intronic sequences flanking each of the 16 exons were obtained from clones of a canine genomic library. Results Using polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP) and DNA sequence analyses we screened affected and unaffected dogs of 23 breeds with presumed autosomal recessively (ar) transmitted gPRA. In the coding region of the SAG gene 12 nucleotide exchanges were identified, 5 of which lead to amino acid substitutions (H14C; A111V; A113T; D259T; A379E). 7 other exonic substitutions represent silent polymorphisms (C132C; Q199Q; H225H; V247V; P264P; T288T and L293L). 16 additional sequence variations were observed in intronic regions of different dog breeds. Conclusions In several breeds, these polymorphisms were found in homozygous state in unaffected and in heterozygous state in affected animals. Consequently these informative substitutions provide evidence to exclude mutations in the SAG gene as causing retinal degeneration in 14 of the 23 dog breeds with presumed ar transmitted gPRA.